A comparison of Lichtenstein repair versus posterior wall repair plus mesh repair for direct inguinal hernias - Goel, Anubhav; Bansal, Ankur; Kumar, Dipt; Pathak, Abhishek (International Surgery Journal, 2017)
Background: Lichtenstein’s tension free mesh repair is the most commonly performed in open inguinal hernias. The present study was done by comparing Lichtenstein Repair (LR) v/s posterior wall repair (PR)+ Lichtenstein repair (LR) of direct Inguinal Hernias to compare the technique of both surgeries and its outcome like postoperative complications and recurrence rate. Methods: This study was conducted in SNMC Agra where patients of unilateral male direct inguinal hernia were included. A total of 60 patients were taken and divided into two groups (A and B) randomly of 30 each. In group A patients were operated by LR and in group B patients were operated by PR+LR and followed up for a period of six months. The outcomes of the both techniques were compared. Results: Mean age was 48.3 years in group A and 49.5 in group B. The mean duration of surgery for group A is around 29.34 min and group B is 46.28 min which was significant. The pain was not statistically significant in both groups on day 1 and 3. There was 1 (3.3%) recurrence in group A and no recurrence in group B. Post-operative complications were similar in both groups. Conclusions: LR+PR were comparatively better than only LR in all direct inguinal hernias because of low recurrence rate (0%).